2018
DOI: 10.1101/251124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Irreversible temperature gating in trpv1 sheds light on channel activation

Abstract: Temperature activated TRP channels or thermoTRPs are among the only proteins that can directly convert temperature changes into changes in channel open probability. In spite of a wealth of information, including several experimentally determined structural models of TRP channels, the mechanism of temperature activation remains unknown. We have carefully characterized the repeated activation of TRPV1 by thermal stimuli and discovered a previously unknown inactivation process, which is irreversible. This inactiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…An important observation is the fact that this structure is not reversible. In accordance with this, we have recently shown that temperature-dependent gating of full length TRPV1 is also irreversible and this irreversibility is reflected in a large hysteresis during the activation processes (49). It is thus possible that the behavior of the ARD observed here could be related to this irreversible gating process.…”
Section: Discussionsupporting
confidence: 65%
“…An important observation is the fact that this structure is not reversible. In accordance with this, we have recently shown that temperature-dependent gating of full length TRPV1 is also irreversible and this irreversibility is reflected in a large hysteresis during the activation processes (49). It is thus possible that the behavior of the ARD observed here could be related to this irreversible gating process.…”
Section: Discussionsupporting
confidence: 65%
“… 30 , 31 The reason for the prolonged pain relief is not clear but may be related to established research that shows pulsed heat at certain temperatures can result in prolonged deactivation of TRPV1 calcium channels. 32 While that research was not done on humans, it is known that capsaicin, a selective TRPV1 channel agent, can cause prolonged desensitization and inactivation of the TRPV1 channel. 33 , 34 In addition, some of the prolonged TRPV1 response may be secondary to change occurring in the dorsal horn or central nervous system as prolonged effects can sometimes be noted with acupuncture like TENS causing a sustained effect that can be reversed by naloxone.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the relatively slow speed (on the second timescale) of preheated solution perfusion to achieve temperature jumps, heat-induced desensitization of TRP channels 18,[26][27][28] could largely affect our measurement of heat-activated threshold. Therefore, we used a laser-based experimental setup for the photothermal effects to achieve rapid heating 16,29 on the cell membranes expressing MrTRPA1 and MrTRPV1 within milliseconds.…”
Section: Heat-activated Thresholds Of Mrtrpa1 and Mrtrpv1mentioning
confidence: 99%